Об усовершенствовании электромеханических устройств управления обмотками бистабильных электромагнитных актуаторов вакуумных выключателей - Бугайчук, В.М.; Емельянов, В.Л.; Ересько, А.В.; Клименко, Б.В. (Електротехніка і електромеханіка, 2011)
We consider the direction of improvement of vacuum circuitbreakers with electromechanical control on the electromagnetic bistable actuator mean stresses. Presents some shemotehtechnical solutions aimed at reducing contact wear, increase performance and decrease voltage trip actuator, as well as decisions regarding the protection of the windings actuator.